PEMURNIAN CRUDE GLYCEROL DENGAN CARA PENGASAMAN DAN ADSORPSI MENGGUNAKAN ZEOLIT ALAM LAMPUNG - Aziz, Isalmi; Las, Thamzil; Shabrina, Annisa (CHEMISTRY PROGRESS, 2014)
This study aims to determine the optimum conditions for the adsorption process and the characteristics ofresulting glycerol after the adsorption process. Raw material for making crude glycerol is used cooking oilobtained from fried food merchants around the campus of UIN Syarif Hidayatullah Jakarta. Crude glycerol wasmade from used transesterification reaction of cooking oil (10 L), methanol (2.5 L) and catalyst KOH (95 g) at 60° C for 1 hour. Crude glycerol is separated from the biodiesel and sulfuric acid 1.19 M was added until pHreached 6 and formed two layers. The bottom layer (rich glycerol) was separated by filtration and glycerol levelswas 60.7%, water was 18.72%, ashes was 35, negative for sugar, potassium metal of 4458 ppm and density of 1.140 g/mL. The next stage is process of adsorption using activated natural zeolite Lampung. Crude glycerol as the result of acidification process was added with activated natural zeolite, stirred, settled and filtered. Adsorption process is done by varying the time (30, 45, 60, 75 and 90 minutes) zeolite concentrations (6, 9, 12, 15 and 18%), temperature (30, 40, 60, 80 and 100 °C) and the size of the zeolite (9, 25 and 60 mesh). The optimum condition of adsorption process was found to be 75 minutes, with 12% zeolite concentration, temperature of 60 °C and the size of the zeolite 0.2 mm with glycerol content of 88.91%, 7.38% water, 3% ashes, contains no sugar and density of 1,231g/mL.Penelitian ini bertujuan untuk menentukan kondisi optimum proses adsorpsi dan karakteristik gliserol yang dihasilkan setelah proses adsorpsi. Bahan baku pembuatan crude glycerol adalah minyak goreng bekas yang diperoleh dari pedagang gorengan disekitar kampus UIN Syarif Hidayatullah Jakarta. Crude glycerol di buat dari reaksi transesterifikasi minyak goreng bekas (10 L), metanol (2,5 L) dan katalis KOH (95 g) pada suhu 60 oC selama 1 jam. Crude glycerol dipisahkan dari biodiesel dan ditambahkan asam sulfat 1,19M sampai pH 6sehingga terbentuk dua lapisan. Lapisan bawah (kaya gliserol) dipisahkan dengan cara penyaringan dan didapatkan kadar gliserol 60,7%, air 18,27%, abu 35, gula negatif, logam kalium 4458 ppm dan massa jenis 1,140 g/mL. Tahap selanjutnya adalah proses adsorpsi menggunakan zeolit alam Lampung yang sudah diaktivasi. Crude glycerol hasil pengasaman ditambahkan zeolit alam teraktivasi, di aduk, didiamkan dandisaring. Proses adsorpsi dilakukan dengan memvariasikan waktu (30, 45, 60, 75 dan 90 menit) konsentrasi zeolit (6, 9, 12, 15 dan 18%), suhu (30, 40, 60, 80 dan 100 oC) dan ukuran zeolit (9, 25 dan 60 mesh). Kondisi optimum proses adsorpsi didapatkan pada waktu 75 menit, konsentrasi zeolit 12%, suhu 60 oC dan ukuran zeolit 0,2 mm dengan kadar gliserol 88,91%, air 7,38%, abu 3%, tidak mengandung gula dan massa jenis 1,231g/mL.